The Translation Strategy for English Fable Text - Akmalkurnia, Roehul Hadi (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Hearing fable word must be familiar to the ear, the form of the text is in simple language, one type of literary work that is usually a bedtime story, with language characteristics that are easy to understand, it is natural that the target readers are children, especially in the millennial era, parents can easily access fable texts from cellphones to tell their children, this analysis has a purpose for building child psychology (Haryadi and Irawan, 2016). The importance of fable texts to build child psychology, challenges often come from translating fable texts, choosing simple words as if there are two sides of a coin due to cultural differences between the source language and target language, translators are required to be creative and innovative in translating fable texts, have extensive knowledge in order to be able to present alternative solutions so as to achieve accurate translation results. The methods and results of this analysis show that this analysis aims to increase the level of knowledge in the field of fable text translation through the selection of translation techniques supported by theory in translation strategy activities. Fables understand the analysis of language style translation techniques, conditional translation techniques, modulation translation techniques, borrowing translation techniques, and transposition translation techniques, these theories are a tool for evaluating.